Sports Nutrition - Current Recommendations - König D; Braun H; Carlsohn A; Großhauser M; Lampen A; Mosler S; Nieß A; Oberritter H; Schäbethal K; Schek A; Stehle P; Virmani K; et al. (Deutsche Zeitschrift für Sportmedizin, 2020)
Carbohydrates are an important source of energy during physical exercise. Carbohydrates lead to a higher energy yield and higher energy flux per liter of oxygen than the oxidation of fatty acids. However, the storage capacity for carbohydrates in liver and muscles is limited.Therefore, athletes performing prolonged endurance or intermittent high-intensity exercise should include a high proportion of carbohydrates in their daily diet. The individual amount depends on body weight and the extent of physical activity. Energy expenditure during physical exercise results in a gradual depletion of carbohydrate stores. The extent to which carbohydrate stores are depleted is dependent on the duration and intensity of exercise.Therefore, particularly during prolonged intense exercise, performance may be improved by consuming an adequate quantity of carbohydrates during exercise. In addition, following a long period of intensive physical activity, rapid post-exercise intake of carbohydrates can help replenish carbohydrate stores more quickly.This position paper sets out current guidelines for the type, quantity and timing of carbohydrate intake in sport. It will also discuss the significance of carbohydrate loading, the glycemic index, and training without prior intake of carbohydrates. Key Words: Carbohydrate Intake, Glycemic Index, Physical Activity, Glycogen Stores, Energy Supply